Inhibition of Aeromonas hydrophila and intestinal pathogenic bacteria in Nile tilapia (Oreochromis niloticus) fish by silver nanoparticles. (Journal of Advanced Veterinary and Animal Research, 2025)
Objective: This research investigated the antibacterial properties of coated silver nanoparticles (CAgNPs) and non-coated silver nanoparticles (NCAgNPs) against bacterial pathogens relevant to Nile tilapia (Oreochromis niloticus), using both in vitro and in vivo methods. Materials and Methods: The antibacterial activity of CAgNPs and NCAgNPs was evaluated in vitro against seven bacterial pathogens: Staphylococcus aureus, Bacillus cereus, Escherichia coli, Aeromonas hydrophila, Listeria monocytogenes, Salmonella enterica, and Aeromonas sobria. For the in vivo assessment, 200 Nile tilapia were divided into five treatment groups. The control treatment group was fed a standard diet, but the four treatment groups were fed the standard diet mixed with either 100 or 200 mg/kg of CAgNPs or NCAgNPs, respectively, and the growth indices, antioxidant parameters, immune functions, and intestinal microbiota were assessed. When the experiment was finished, 20 fish of every group were infected with A. hydrophila. Results: In vitro assays demonstrated significant antibacterial activity of both CAgNPs and NCAgNPs at 200 µg/ml (p < 0.05) against every bacterial strain that was studied, with moderate activity observed at 100 µg/ml. CAgNPs exhibited larger inhibition zones (30.0 ± 0.58 mm to 36.33 ± 0.88 mm) compared to NCAgNPs, with a minimum inhibitory concentration of 150 µg/ ml. Dietary supplementation with 200 mg/kg CAgNPs improved growth performance, enhanced immune parameters, reduced oxidative stress, and decreased intestinal bacterial load in Nile tilapia. Furthermore, dietary supplementation with 100 mg/kg CAgNPs was more efficient than 100 mg/kg NCAgNPs in reducing intestinal bacterial colonization in fish. Conclusion: These findings indicate the possibility of CAgNPs as an efficient antimicrobial factor in aquaculture. CAgNPs may offer a promising alternative to conventional antibiotics by improving tilapia health and antioxidant status, enhancing immune function, and increasing disease resistance.J. Adv. Vet. Anim. Res., 12(2): 647–660, June 2025http://doi.org/10.5455/javar.2025.l928